2013
DOI: 10.15376/biores.8.2.2583-2593
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Fiber Board Coated with Nano Kaolin-Clay Film

Abstract: Fiberboard is a common interior material used both in China and the United States of America. The increase in demand for interior materials has raised concerns regarding combustibility of the materials. The pyrolysis characteristics of fiber, phenolic resin (PF), and nano kaolinclay (NK) were investigated using thermogravimetry. The fire performances of samples coated with a mixture of NK and PF were determined using a cone calorimeter. The pyrolysis process of fiber included three phases dependent on chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Both silica and alumina sheets participate in the apical O atoms . The chemical structure of K initiated many researchers to use modified K and K with IFR systems as flame retardant for polymers such as natural rubber, PP, fibre board, and polyurethane foam . Sahnoun and Bouaziz reported that the reaction of phosphoric acid and K can lead to a new phase from aluminium phosphate .…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Both silica and alumina sheets participate in the apical O atoms . The chemical structure of K initiated many researchers to use modified K and K with IFR systems as flame retardant for polymers such as natural rubber, PP, fibre board, and polyurethane foam . Sahnoun and Bouaziz reported that the reaction of phosphoric acid and K can lead to a new phase from aluminium phosphate .…”
Section: Introductionmentioning
confidence: 55%
“…[16][17][18] The chemical structure of K initiated many researchers to use modified K and K with IFR systems as flame retardant for polymers such as natural rubber, PP, fibre board, and polyurethane foam. [17][18][19][20][21] Sahnoun and Bouaziz reported that the reaction of phosphoric acid and K can lead to a new phase from aluminium phosphate. 22 However, the attempt to combine K with pentaerythritol phosphate and melamine as a single molecule IFR was not studied in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As shown on the TG curves, the untreated and treated samples underwent three degradation steps. The first degradation step of the mass loss was in the temperature range of 30 ℃ to 245 C, which is due to the removal of water from the samples (Liu et al 2013). The mass loss of the treated samples at 200 C were greater than 5%, which was due to the catalytic dehydration of monoammonium phosphate.…”
Section: Thermal Propertiesmentioning
confidence: 97%